Main organiser (conception, call for papers, dissemination, evaluation of proposals via blind review, organisation of panels, logistics, chair of panels) - Venizelos, Giorgos (My University, 2026)
https://www.psa.ac.uk/specialist-groups/group-events/call-papers-%E2%80%93-populism-and-aesthetics-%E2%80%93-7th-annual-psa-populism